Pelatihan Software Kimia Komputasi Berbasis Web pada Guru-Guru Kimia di Samarinda: Web-based Computational Chemistry Software Training for Highschool Teacher in Samarinda - Londong Allo, Veliyana; Subagyono, Raden Roro Dirgarini Julia Nurlianti; Gunawan, Rahmat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Chemistry is one of the subjects of interest at the senior high school level, but due to limited resources, understanding of the subject remains abstract. The challenge faced by chemistry teachers at the high school level, especially in Samarinda City, is to convey material clearly and make it easy for students to understand. Learning media are needed in lessons, which can be a solution for chemistry teachers in schools. Web-based Computational Chemistry Software Training is one of the interactive learning media that chemistry teachers can use to provide a clear picture of abstract chemical concepts. The method used in this service is training for chemistry teachers on the use of Web-based Computational Chemistry Software, namely GAMESS, followed by independent tutorials and discussions on the development of computational chemistry. This training showed that most participants showed significant progress in mastering the GAMESS software and enthusiasm for applying it in teaching and learning activities. Based on the evaluation results, a follow-up plan in mentoring or further training will be considered to ensure the sustainable implementation of computational chemistry technology in schools in Samarinda.